TEST OF PERFOMANCE ERK HYBRID DRYER WITH BIOMASS FURNACE AS ADDITIONAL HEATING SYSTEM FOR NUTMEG SEED (Myristica sp.) DRYING - Guyup Mahardhian Dwi Putra (The University of Lampung, 2014)
Conventional drying depend on the weather. It was caused agricultural product damaged, and moldy attack. So we need hybrid dryer with a source of radiation and solar biomass to continuous drying and can be controlled.The aims of this research is test performance of ERK hybrid dryer to drying the nutmeg seed during the drying process. Experiments were conducted to determine the distribution of temperature in the dryer in condition with no material and material conditions. Input of energy derived from biomass combustion in the furnace (evening) and combination of biomass and radiation (during the day). Measurements of temperature and RH using a thermocouple CC and alcohol thermometer. Temperature and RH to be measured include temperature and RH in dryer with several measurement points representing the up, middle , bottom and inlet temperature, outlet temperature and ambient temperature measurements at intervals of 30 minutes. The results showed average temperature ranges between 42 ° C - 51 ° C and RH ranged between 50.96 % -55.65 % . Time of drying is used to dry nutmeg from the initial moisture content from 80.72 % wb to 9.67 % wb is 52 hours with an average drying rate is 7.8 % db / hour . The total energy used to heat and vaporize materials,water that is 290 499.9 kJ. Efficiency of drying system 8.63% and energy of drying required to water evaporated is 28520.62 kJ / kg. The result quality of product obtained color of nutmeg generally more uniform.Key word : nutmeg seed, drying, green house, efficiency.